O desenvolvimento da competência leitora no Ensino Fundamental na Rede Estadual de Ensino de São Paulo - Silva, Ednaldo Torres da (2022)
The results of the 2019 São Paulo State School Performance Assessment System (Saresp) revealed that most 9th grade students demonstrated proficiency levels corresponding to what they showed when they were in 5th grade (Brazilian education system).Thus, driven by concerns about the teaching of reading in public schools, specifically in elementary level, this research aimed to investigate how the teacher can contribute to the training of reading of 9th grade students in the São Paulo State public education network. The specific objectives were: to identify if there are differences regarding the practices of the teaching of reading developed in the 5th and 9th grades of elementary school; to verify if the teaching of reading practices have changed due to the social distancing imposed by the Covid-19 pandemic, and to present remarks which help the teaching of reading process in the 9th grade of elementary school. The study started from the hypothesis that the teaching of reading, through strategic procedures, can enhance the development of students’ reading competence; more specifically, that the teacher, as a mediator, must invest in metacognitive strategies to promote conditions for improving students' reading competence. The building of the theoretical framework was based on studies about the teaching of reading in school and reading strategies. Since this is a qualitative study, the data production tool used was individual semi-structured interviews with teachers, teacher coordinators (so-called PCs), and teacher coordinators of the Pedagogic Centre (so-called PCNPs) of the Elementary School in São Paulo State education network, summing up 10 participants. The data analysis, based on the content analysis methodology, pointed out that, in many the teaching of reading practices, the text was not explored to its full potential, since the reading strategies, when used by some research participants, were not deepened, or were transformed into mechanistic reading techniques without reflection on what the texts would enable us to think carefully. Maybe that is why these strategies have not contributed to the training of proficient readers